2003
DOI: 10.1074/jbc.m305361200
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator-activated Receptor α Induces Hepatic Expression of the Human Bile Acid Glucuronidating UDP-glucuronosyltransferase 2B4 Enzyme

Abstract: Glucuronidation, a major metabolic pathway for a large variety of endobiotics and xenobiotics, is catalyzed by enzymes belonging to the UDP-glucuronosyltransferase (UGT) family. Among UGT enzymes, UGT2B4 conjugates a large variety of endogenous and exogenous molecules and is considered to be the major bile acid conjugating UGT enzyme in human liver. In the present study, we identify UGT2B4 as a novel target gene of the nuclear receptor peroxisome proliferatoractivated receptor ␣ (PPAR␣), which mediates the hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
87
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(89 citation statements)
references
References 63 publications
(60 reference statements)
1
87
1
Order By: Relevance
“…These results suggest that the increases in the hepatic ascorbic acid concentration and its urinary excretion by dietary sesame seed in Wistar rats are due to the stimulation of ascorbic acid biosynthesis by the induction of a UGT1A/2B-mediated metabolism of sesame lignan or its metabolite. Sugano et al (40)(41)(42) have shown that dietary sesamin stimulates the expression of several genes related to fatty acid metabolism, and have suggested that sesamin is a ligand of peroxisome proliferator-activated receptor ␣, which induces hepatic UGT2B gene expression (43). Therefore, dietary sesamin may stimulate UGT2B gene expression by activating peroxisome proliferator-activated receptor ␣.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the increases in the hepatic ascorbic acid concentration and its urinary excretion by dietary sesame seed in Wistar rats are due to the stimulation of ascorbic acid biosynthesis by the induction of a UGT1A/2B-mediated metabolism of sesame lignan or its metabolite. Sugano et al (40)(41)(42) have shown that dietary sesamin stimulates the expression of several genes related to fatty acid metabolism, and have suggested that sesamin is a ligand of peroxisome proliferator-activated receptor ␣, which induces hepatic UGT2B gene expression (43). Therefore, dietary sesamin may stimulate UGT2B gene expression by activating peroxisome proliferator-activated receptor ␣.…”
Section: Discussionmentioning
confidence: 99%
“…CYP4 family members were the first fibrate-induced XME target genes shown to be involved in omega-hydroxylation of fatty acids [5]. PPARα is involved in regulation of all phases of the XME system including regulation of many UGTs (UGT1A1, 1A3, 1A4 [51], 1A9 [52], 2B4 [53]). PPARα-induced hepatic UGTs are possibly involved in detoxification of eicosanoids, as discussed in section 4.4.…”
Section: Pparαmentioning
confidence: 99%
“…17 HepG2 cells were grown as described. 19,20 For RNA analyses, 10 6 HepG2 cells were treated with the indicated concentration of LXR␣ activators for the indicated duration, in the absence or presence of cycloheximide or after a 2-hour pretreatment with actinomycin D. For glucuronidation assays, 20 ϫ 10 6 HepG2 cells were treated with T0901317 (10 mol/L) for 36 hours, and cells were harvested for subsequent purification of microsomes.…”
Section: Methodsmentioning
confidence: 99%
“…Oligonucleotides and PCR conditions for 18S were as previously described. 19,20 Quantitative PCR analyses of UGT1A3 mRNA levels were determined using primers as indicated in Table 1. Conditions for real-time PCR were 95°C for 10 minutes, 95°C for 15 seconds, and 66°C for 60 seconds for 40 cycles.…”
Section: Methodsmentioning
confidence: 99%